Interstellar dehydrogenated PAH anions: vibrational spectra. Issue 4 (27th November 2017) - Buragohain, Mridusmita; Pathak, Amit; Sarre, Peter; Gour, Nand Kishor
Abstract: Interstellar polycyclic aromatic hydrocarbon (PAH) molecules exist in diverse forms depending on the local physical environment. Formation of ionized PAHs (anions and cations) is favourable in the extreme conditions of the interstellar medium (ISM). Besides in their pure form, PAHs are also likely to exist in substituted forms; for example, PAHs with functional groups, dehydrogenated PAHs etc. A dehydrogenated PAH molecule might subsequently form fullerenes in the ISM as a result of ongoing chemical processes. This work presents a density functional theory (DFT) calculation on dehydrogenated PAH anions to explore the infrared emission spectra of these molecules and discuss any possible contribution towards observed IR features in the ISM. The results suggest that dehydrogenated PAH anions might be significantly contributing to the 3.3 μm region. Spectroscopic features unique to dehydrogenated PAH anions are highlighted that may be used for their possible identification in the ISM. A comparison has also been made to see the size effect on spectra of these PAHs.